2019
DOI: 10.1063/1.5099325
|View full text |Cite
|
Sign up to set email alerts
|

In-situ high temperature micro-Raman investigation of annealing behavior of high-pressure phases of Si

Abstract: Among the 13 polymorphic phases of Si, the ambient temperature stable body-centered cubic (bc8) and rhombohedral (r8) polymorphs have gained significant interest due to their attractive optical and electronic properties suitable for photovoltaic applications. Though ex situ methods were extensively employed previously to understand the pressure-induced phase transformation kinetics of Si, the limited number of available in situ studies has significantly improved the knowledge in this field and clarified uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The increased peak positions mean shortened bond lengths, which can be detected in compressive stress zones during annealing. 49,50 Therefore, the results suggest that compressive stress is emerged with elevated temperature. The formed compressive stress probably originates from the different thermal motion of the disordered structures and ordered structures.…”
mentioning
confidence: 87%
“…The increased peak positions mean shortened bond lengths, which can be detected in compressive stress zones during annealing. 49,50 Therefore, the results suggest that compressive stress is emerged with elevated temperature. The formed compressive stress probably originates from the different thermal motion of the disordered structures and ordered structures.…”
mentioning
confidence: 87%
“…It is indeed interesting to observe twinning in the diamond cubic crystal structure at 150-200 C. It is reported that beyond 300-400 C, deformation by slip can cause significant plasticity in Si. [261] With the knowledge obtained from the in situ electrical and high-temperature measurements, such as electrical and annealing behavior of the R8 phase of Si, [262] recently, Sowjanya et al [263] fabricated the large-area R8 phase in a dc-Si wafer using spherical nanoindentation and studied the optical properties, and utilized it for solar applications. The UV-vis optical spectrum showed a 50% lower reflectance for the R8 phase compared to the dc-Si.…”
Section: Phase Transformations In Simentioning
confidence: 99%